2018
DOI: 10.3390/molecules23092261
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric Comparison and Classification of Some Essential Oils Extracted from Plants Belonging to Apiaceae and Lamiaceae Families Based on Their Chemical Composition and Biological Activities

Abstract: This study is focused on the comparison and classification of parsley, lovage, basil, and thyme essential oils (EOs) based on their chemical composition, total phenolic content, antioxidant and antibacterial activities by using appropriate chemometric methods: Principal component analysis (PCA) and hierarchical cluster analysis (HCA). The results showed that parsley, lovage, and thyme EOs are rich in monoterpene hydrocarbons, but basil EO is rich in oxygenated monoterpenes and phenylpropanoids, and that both P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 27 publications
(36 reference statements)
0
37
1
Order By: Relevance
“…The essential oil of tarragon was dried over anhydrous sodium sulphate and stored at 4 °C prior to analysis. The extraction yield was calculated as the volume of essential oil (mL) per dried leaves’ weight (g) and multiplied by 100 [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The essential oil of tarragon was dried over anhydrous sodium sulphate and stored at 4 °C prior to analysis. The extraction yield was calculated as the volume of essential oil (mL) per dried leaves’ weight (g) and multiplied by 100 [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative ITEX/GC-MS (in-tube extraction coupled with gas chromatography-mass spectrometry) analysis of volatile constituents was carried out as described in our previous report [ 5 ]. A sample of 1 µL volume was measured into a sealed-cap headspace vial (20 mL) and maintained on continuous agitation at 60 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…but against H 2 S producing bacteria and lactic acid bacteria, the one with 3% oregano EO under the MAP. Different inhibitory effects displayed by an essential oil against various bacteria are most probably due to its chemical composition [35]. The antimicrobial mechanism of action of plant EOs is related to the hydrophobicity of their components [36], which enables them to migrate in the lipids of the bacterial cell membrane and mitochondria, disturbing their structures and rendering them more permeable [37]; leakage of ions and intracellular constituents can thus occur [38].…”
Section: Efficacy Against Spoilage Microorganismsmentioning
confidence: 99%
“…However, many studies revealed the negative effects of synthetic food preservatives on human health and the increasing resistance of microorganisms to these compounds. As a result, researchers are focused on the identification and use of natural preservatives like essential oils (EOs), which are volatile liquids distilled from different aromatic plant materials [4][5][6][7]. EOs from Origanum vulgare L. (oregano -OrEO) and Mintha piperita (mint -MiEO) are effective in inhibiting a range of cheeserelated bacteria in vitro systems, making them a key alternatives for cheese preservation [8].…”
Section: Introductionmentioning
confidence: 99%